Comparison of Direct and Mediated Electron Transfer for Bilirubin Oxidase from Myrothecium Verrucaria. Effects of Inhibitors and Temperature on the Oxygen Reduction Reaction - Sanchez-Poblete, J; Tasca-Gottardo, F; Tasca-Gottardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
One of the processes most studied in bioenergetic systems in recent years is the oxygen reduction reaction (ORR). An important challenge in bioelectrochemistry is to achieve this reaction under physiological conditions. In this study, we used bilirubin oxidase (BOD) from Myrothecium verrucaria, a subclass of multicopper oxidases (MCOs), to catalyse the ORR to water via four electrons in physiological conditions. The active site of BOD, the T2/T3 cluster, contains three Cu atoms classified as T2, T3α, and T3β depending on their spectroscopic characteristics. A fourth Cu atom; the T1 cluster acts as a relay of electrons to the T2/T3 cluster. Graphite electrodes were modified with BOD and the direct electron transfer (DET) to the enzyme, and the mediated electron transfer (MET) using an osmium polymer (OsP) as a redox mediator, were compared. As a result, an alternative resting (AR) form was observed in the catalytic cycle of BOD. In the absence and presence of the redox mediator, the AR direct reduction occurs through the trinuclear site (TNC) via T1, specifically activated at low potentials in which T2 and T3α of the TNC are reduced and T3β is oxidized. A comparative study between the DET and MET was conducted at various pH and temperatures, considering the influence of inhibitors like H2O2, F-, and Cl-. In the presence of H2O2 and F-, these bind to the TNC in a non-competitive reversible inhibition of O2. Instead; Cl- acts as a competitive inhibitor for the electron donor substrate and binds to the T1 site. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.